Integrating music in the makabayan learning areas - Nastor, Evelyn J. (2007)
A new integrated learning called the Makabayan was introduced in June 2002 consisting of 4 integrated disciplines. This study aimed to find ways of integrating Music in Makabayan. Analysis of the contents of the elementary learning competencies (ELC) was done to find out what general and specific musical concepts and skills are included. Four general music concepts emerged: Performance, Reading and Writing, Listening and Background Knowledge. Specific concepts were also identified. This study recommended the use of interdisciplinary model using thematic approach in combination with other variants like whole-language approach and inquiry approach.